Kajian Meteorologis Bencana Banjir Bandang Berbasis Data Satelit Himawari-9 dan Model ECMWF (Studi Kasus: Banjir Bandang Luwu 2 Mei 2024) - Panji Kuswanaji; Yahya Darmawan; Widodo Widodo; Nuzula Elfa Rahma; Rizky Franchitika (Jurnal Penelitian Sains, 2026)
Flash floods are sudden floods with large volumes. Flash floods are generally caused by continuous or extreme rainfall that causes the soil to become saturated so that it can no longer absorb water. On May 2, 2024, data from AAWS Bajo recorded high rainfall with the highest value of 94.6 mm/hour in Luwu Regency and its surroundings. This study aims to analyze the flash flood event in Luwu Regency on May 2, 2024 using Himawari-9 weather satellite data and the ECMWF model. The results showed the presence of convective clouds or high Cumulonimbus indicated by the low cloud top temperature of -72.5Â°C, dark red cloud assemblies on satellite images with RGB 24-hour microphysics technique, and convective cloud patterns on the Cloud Convective Overlay technique outplot. By analyzing the atmospheric conditions at the time of the event, it was found that the divergence value was < -0.00015; RH value was 90-110%; wind slowing pattern, and warmer sea surface temperature. The AUSMI and WNPMI monsoon index values indicated a weakening of the Australian monsoon and an increase in monsoon winds carrying higher humidity. These atmospheric and monsoon conditions were very favorable for convective cloud growth that caused the extreme rainfall that resulted in flash floods in Luwu District.